Impact of haemoconcentration during acute heart failure therapy on mortality and its relationship with worsening renal function. (19th October 2016) - Breidthardt, Tobias; Weidmann, Zoraida Moreno; Twerenbold, Raphael; Gantenbein, Claudine; Stallone, Fabio; Rentsch, Katharina; Rubini Gimenez, Maria; Kozhuharov, Nikola; Sabti, Zaid; Breitenbücher, Dominik; Wildi, Karin; Puelacher, Christian; et al.
Abstract: Aims: Treatment goals in acute heart failure (AHF) are poorly defined. We aimed to characterize further the impact of in‐hospital haemoconcentration and worsening renal function (WRF) on short‐ and long‐term mortality. Methods and results: Haematocrit, haemoglobin, total protein, serum creatinine, and albumin levels were measured serially in 1019 prospectively enrolled AHF patients. Haemoconcentration was defined as an increase in at least three of four of the haemoconcentration‐defining parameters above admission values at any time during the hospitalization. Patients were divided into early (Day 1–4) and late haemoconcentration (>Day 4). Ninety‐day mortality was the primary endpoint. Haemoconcentration occurred in 392 (38.5%) patients, with a similar incidence of the early (44.6%) and late (55.4%) phenotype. Signs of decongestion (reduction in BNP blood concentrations, P = 0.003; weight loss, P = 0.002) were significantly more pronounced in haemoconcentration patients. WRF was more common in haemoconcentration patients ( P = 0.04). After adjustment for established risk factors for AHF mortality, including WRF and HF therapy at discharge, haemoconcentration was significantly associated with a reduction in 90‐day mortality [hazard ratio (HR) 0.59, 95% confidence interval (CI) 0.37–0.95, P = 0.01]. The beneficial effect of haemoconcentration seemed to be exclusive for late haemoconcentration (late vs. early: adjusted HR 0.41, 95% CI 0.19–0.90, P = 0.03) and persisted in patients with or without WRF. Conclusions: Haemoconcentration represents an inexpensive and easily assessable pathophysiological signal of adequate decongestion in AHF and is associated with lower mortality. WRF in the setting of haemoconcentration does not appear to offset the benefits of haemoconcentration.